Growth and quality of the post-weaned hairless pig carcass fed with tree plant foliage meal - Castellón M., Claudia Teresita (2024)
The aim of the study was to compare the inclusion of 10% leaf meal from the trees Cnidoscolus aconitifolius (chaya), Morus alba (mulberry) and Moringa oleifera (moringa) in the conventional corn-soybean meal diet of post-weaning pigs of the Mexican Hairless Pig (Cerdo Pelón Mexicano) to improve growth and carcass quality parameters. In total, 28 24-day-old piglets were used, distributed in four experimental groups similar in number, sex and weight. The animals were fed ad libitum for 28 days and slaughtered at 59 days of age with a final weight of 6.8 ± 0.3 kg. A completely randomized block design statistical model was used with the initial weight as covariance. The variables final weight, daily weight gain, carcass length and thorax roundness were greater (p<0.05) in the groups fed with chaya and moringa. The thickness of the dorsal fat decreased with the use of foliage trees in the diets. The colorimetric variables a, b and C index presented higher values (p<0.05) in the chaya and Control treatments. It is concluded that foliage tree meals decrease the thickness of dorsal fat, that chaya and moringa increase the values in the growth parameters and chaya increases the quality of the meat of the post-weaning hairless piglets.